Mother's Motivation as a Factor Related to Exclusive Breastfeeding - Ghefira Dania; Poppy Fitriyani (Jurnal Ilmu Keperawatan Jiwa, 2020)
The Exposure to The Promotion of Dairy Substitute for Breast Milk and Maternal Motivation As a Factor for Exclusive Breastfeeding. The importance of exclusive breastfeeding has promulgated in health programs, laws, and regulations by Indonesia's Government. However, the rate of exclusive breastfeeding in Indonesia is still low, especially in DKI Jakarta. This research conducted to determine the correlation between maternal motivation to breastfeed exclusively in DKI Jakarta. This type of research is quantitative with a cross-sectional approach. Retrieval data performed on 100 mothers who have babies aged between 7 to 24 months in DKI Jakarta using the consecutive sampling method by filling out an online questionnaire. From this research, it obtained that there was there is a significant correlation between maternal motivation with exclusive breastfeeding (p0,000>α0,005) with OR=6,7667 (95%CI:2,702-16,947) where the high motivation in giving breast milk 6.77 times more potential to be able to give her baby exclusive breastfeeding.